BOOKS BY JURGIS PLATERIS IN VILNIUS UNIVERSITY LIBRARY - Rankelienė, Sondra (Knygotyra, 2016)
The article aims to provide analysis of 25 newly identified books from the personal library of the Lithuanian language and writing researcher, bibliographer Jurgis Plateris (Jerzy Plater, 1810–1836); present their thorough bibliographic descriptions with encoded provenances embedded in these books. On the basis of new research data, an updated version of J. Plater’s personal library, described in the monography by Domas Kaunas Bibliotheca Georgii comitis de Plater: Jurgio Platerio biblioteka – Lietuvos knygos kultūros ir mokslo paminklas (Jerzy Plater’s library – a monument of Lithuanian Book Culture and Science. Vilnius, 2012, in Lithuanian), has been presented. Plater’s library image has been update from the thematic, chronological and linguistic points of view. It has been established that currently, in total 116 titles of documents stored in Plater’s library have survived, among them 100 books, 6 scientific journals, the number of graphics and manuscript documents has not changed (one document of graphics) and 9 manuscripts. Given the insignificant number of surviving bibliographic items of Plater’s library, one cannot claim that Jerzy Plater was interested exclusively in one specific field of science or public activities. His library contained historical, legal, linguistic, philosophical and literary items, as well as those from folklore, natural sciences and religion. The available sources lead us to believe that the surviving part of Plater’s personal library is dominated by historical and legal treatises published in the 18–19th centuries in German and Latin languages. There was not a single item attributed to technical and engineering fields, sciences (mathematics and physics), chemistry or medicine. Judging by the surviving documents, the majority of publications were in German, with a lesser number of publications in Latin, Polish, Lithuanian, French and other languages. We cannot claim that all the books stored in Vilnius University library that once belonged to Plater’s personal library have been discovered so far. There is a high likelihood that some ‘hidden’ books (in particular, in the stock of non-Lithuanian books published in the 19th century) might still be discovered. They could contribute to enriching and specifying the big Picture of a most interesting personal library dating back to the start of the 19th century.
Keywords: ...